Vulnerability Analysis of Catenary-Bridge-Track System - Yan, Bin; Yu, Limei; Li, Zhe; Zeng, Zhiping (Shock and Vibration, 2023)
Continuous welded rails on bridges are extensively employed in high-speed railways, where trains are predominantly electrically powered, and the open-air catenary represents the weakest link in the system. Despite the widespread use of continuous welded rail on bridges for high-speed railways, there exists a relative dearth of research on their vulnerability, particularly regarding seismic vulnerability studies that consider the catenary, track type, and bridge collectively. The vulnerability of fasteners and catenary on bridges under the longitudinal resistance of the line was investigated by constructing a 7−32 m high-speed railway double-line simply-supported box girder bridge. It reveals, for the first time, the influence of the longitudinal resistance of the line on the vulnerability of fasteners and catenary under seismic action. The study indicates that both the fasteners’ and catenary’s vulnerability increases with the intensity of ground shaking, with the catenary being more susceptible. The longitudinal resistance of the line has a greater impact on the fasteners’ vulnerability than the catenary. When the degree of damage is minimal, the order of damage to the fasteners is the ballasted track, small resistance fastener, and ballastless track when the probability of exceedance is 5%. The ballastless track can significantly increase the probability of no damage to the fasteners, and it is recommended that the ballastless track be used when designing high-speed railway bridges in earthquake-prone regions.